Factors influencing consumer satisfaction towards online food delivery services among students in Universiti Putra Malaysia - Mohd Rashid Lee, Siti Aisyah; Abu Bakar, Elistina (Persatuan Ekonomi Pengguna dan Keluarga Malaysia (MACFEA), 2023)
The primary purpose of this study was to determine the influencing factors of consumer satisfaction: perceived ease of use, perceived usefulness, social influence, sales promotion and trust towards Online Food Delivery Services (OFDS) among students in Universiti Putra Malaysia. This study applied the Technology Acceptance Model (TAM) by integrating with other factors, social influence, sales promotion, and trust, which may provide insight for food service industry management in developing strategies for OFDS. A total of 200 respondents participated in this study, which was chosen through a simple random sampling method. The results from multiple regression analysis have indicated a significant relationship between perceived ease of use, perceived usefulness, social influence, sales promotion, and consumer satisfaction. In contrast, trust did not significantly explain the variance in consumer satisfaction. In addition, the multiple regression analysis results demonstrated that perceived usefulness was the most dominant factor influencing consumer satisfaction toward OFDS. The result showed that the studied factors explain 59.7 of the variance in satisfaction. The findings benefit policymakers and industries to develop effective strategies to improve customer satisfaction and loyalty.